The Constitutionality of State Authority Over Water Resources Management Based on Human Rights Principles - Ricko Anas Extrada; Kamarusdiana Kamarusdiana (STAATSRECHT: Indonesian Constitutional Law Journal, 2021)
This study intends to investigate the contrast between the private sector's implementation of water privatization in Indonesia and the state's responsibility for managing water resources in light of human rights standards. In accordance with the mandate of the constitution, which states in Article 33, paragraph 3, that "Earth and water, as well as the natural resources contained therein, are under the control of the state and used for the greatest prosperity of the people," the state controls and uses all natural resources for the benefit of the people. This research employs normative legal research methods, while its methodology is a statutory approach, library research methods, and a conceptual approach that will be harmonized with statutory provisions. According to the findings of this study, the state is responsible for managing water resources in compliance with the constitutional requirement to ensure, defend, and fulfill human rights to water. Water administration by the private sector (water privatization) that is monopolistic, exclusive, and materialistic is contrary to the spirit of the Indonesian constitution and the foundation of the nation. In addition, based on the decision of the Constitutional Court to invalidate the Water Resources Law, it mandates that the state manage water resources for the sake of societal welfare.